PRODUKTIVITAS KINERJA GURU DAN MOTIVASI MENGAJAR - Jamiluddin Yacub (LPPM STAI DARUSSALAM LAMPUNG, 2012)
Two factors determine the productivity of work so the teacher is the abilityand willingness to teach, skills related to competence resulting from thelevel of education while teaching a willingness to do with motivation.Work productivity associated with the ratio between output and inputsused to produce outputs. An organization of educational institutions bothgovernment and private sector in issuing its products always require inputin the form of raw materials, capital, energy, technology, human resources(HR), and so forth. But the most urgent input is itself a human resource forsophisticated and complete as any other input if human resources are notworking then all the input there would be no meaning. The quality of humanresources is determined from the level of education the longer time spenton education, the higher ability or competence in doing the work, so thehigher the productivity of its work. In addition to educational level of laborproductivity is also determined by the motivation is strong encouragementfrom the man to conduct their activities in order to achieve the goal, it issaid that 90% of success is determined by the motivation of a person›s lifewhile 10% is determined by intelligence.